Perbandingan Kualitas 3D Objek Tugu Budaya Saibatin Berdasarkan Posisi Gambar Fotogrametri Jarak Dekat - Ade Surahman; Agung Deni Wahyudi; Ade Dwi Putra; Sanriomi Sintaro; Idrajat Pangestu (Universitas Islam Sumatera Utara, 2021)
The Cultural Statistics in 2019 recorded the number of traditional bridal clothing in Lampung province, the Saibatin wedding dress. The wedding dress of Saibatin in the city of Bandar Lampung was made a monument so that it has become a cultural heritage recorded by the Ministry. Therefore, preservation is necessary to protect the monument building. To preserve the steps that will be carried out by this research are reconstruction and conservation, this process is in the form of documentation that is making 3D modeling of objects and shows that the visualization quality of the cultural monument of Saibatin with the technique of making 3D objects with CRF or Close Distance Photogrammetry produces visualization. very good saibatin cultural monument with a record of the number of photos used 400 pictures with a combination of 900 and 450 shots.